Muzyczna nowoczesność. O Pamiętniku Tadeusza Jaroszyńskiego - Koczkodaj, Izabela (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2012)
The article is devoted to analyzing the vision of Modernity and modern life in Tadeusz Jaroszyński’ s short story The Gramophone. The fear of gramophone is an obsession of the main character of the text; it also serves as a pretext to show the 19th century insanity of visuality and sensuality as well. I tried to show that man living in an early Modernity is lost in abudance of sensual impressions which are connected with the big city existence. As Jaroszyński shows, writing a diary is the only way to rescue the humanity of the main character — but it cannot stop him from suicide. Modernity in The Gramophone is showed as a unstopable hostile process which destroys human being.